Al-Zarnuji's Concept of 'Ilm and Fiqh: Its Relevance in the Era of Learning 5.0 - Fardan Basith; Ateng Ruhendi; Izzudin Musthafa; Eva Saufana (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2026)
The emergence of Learning 5.0 has transformed educational paradigms by emphasizing not only technological advancement but also human values, ethical awareness, and holistic development. In Islamic educational thought, the concepts of ‘ilm (knowledge) and fiqh articulated by Al-Zarnuji in Ta‘lim al-Muta‘allim provide a philosophical foundation for addressing these contemporary challenges. This study aims to examine the nature of ‘ilm and fiqh in Al-Zarnuji’s educational perspective and analyze their relevance to the educational orientation of Learning 5.0. This research employs a library research method using conceptual and interpretive analysis of classical Islamic texts and contemporary scholarly literature. The findings reveal that Al-Zarnuji understands ‘ilm not merely as the acquisition of information but as a process of developing moral character, spiritual awareness, and beneficial action. Meanwhile, fiqh refers to the ability to comprehend, contextualize, and apply knowledge wisely in practical situations. These concepts highlight the integration of intellectual, ethical, and spiritual dimensions in the learning process. In the context of Learning 5.0, where technology functions as a tool to support human-centered education, Al-Zarnuji’s ideas offer an ethical framework for balancing technological innovation with character formation and social responsibility. The study contributes to contemporary educational discourse by reinterpreting classical Islamic educational concepts as a holistic foundation for developing adaptive, value-oriented, and human-centered learning models in the digital era.